Music reduces patient-reported pain and anxiety and should be routinely offered during flexible cystoscopy: Outcomes of a systematic review. Issue 4 (2nd October 2021) - Gauba, Anusha; Ramachandra, Meghana N.; Saraogi, Mansi; Geraghty, Robert; Hameed, B.M. Zeeshan; Abumarzouk, Omar; Somani, Bhaskar K.
ABSTRACT: Objective : To conduct a systematic review of the literature to assess whether music reduces the use of analgesics and anxiolytics during flexible cystoscopy. Methods : The systematic review was performed in line with the Cochrane guidelines and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) checklist. The databases searched included the Medical Literature Analysis and Retrieval System Online (MEDLINE), Scopus, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Clinicaltrials.gov, the Excerpta Medica dataBASE (EMBASE), Cochrane library, Google Scholar, and Web of Science from inception of the databases to February 2020. The primary outcome measure was the effect of music on pain and anxiety, and secondary outcome measures were patient heart rate and blood pressure. Results : The initial search yielded 234 articles and after going through titles and abstracts, four studies (399 patients, 199 in the music group and 200 in no music group) were included for the final review. There were three randomised controlled trials and one prospective study published between 2014 and 2017. These studies were done in China, the USA and Italy, with the study duration between 9 and 24 months. All patients had 2% topical lignocaine jelly given per-urethra before the procedure. The choice of music was classical in three studies and a mixture of different music types in one study. Three of the four studies showed significantly reduced pain and anxiety with the use of music for flexible cystoscopy procedures. Heart rate was noted to be higher for the no music group, reflecting a higher pain perceived by these patients. Conclusion : The present review showed that listening to music was associated with reduced anxiety and pain during flexible cystoscopy. Listening to music is therefore likely to increase procedural satisfaction and willingness to undergo the procedure again, considering repeated flexible cystoscopy is often needed for surveillance. As music is simple, inexpensive and easily accessible, it should be routinely offered to patients for outpatient and office-based urological procedures. Abbreviations : IQR: interquartile range; NRS: numerical rating scale; PTSD: post-traumatic stress disorder; RCT: randomised control trial; STAI: State–trait Anxiety Inventory; VAS: visual analogue scale